Komunikasi Dakwah Kultural di Era Millennial - Deni Irawan; Suriadi Suriadi (Alhadharah: Jurnal Ilmu Dakwah, 2020)
Cultural values in the community are gradually being replaced. Children more easily receive information provided by internet media. Right and wrong are still questions because what is received, read, seen and heard from various sources is unclear. Especially if it is associated with Islamic nuances, namely da'wah, it will be a great homework for da'wah interpreters to straighten the news or information that is often found in the community so that people start to be sheepfolded by hoax information that will obviously harm our society. Therefore, it is imperative that efforts be made to filter people out of false news and misleading behavior so that the community becomes an intelligent society, with morality, accompanied by local wisdom nuances that are still maintained as an adhesive between the relationship between the people in this millennial era.